Purification of Used Cooking Oil Using (Tamarindus indica L.) Seeds - Fauzhia, Hariati; Jura, Minarni Rama; Ningsih, Purnama (Jurnal Akademika Kimia, 2019)
Adsorbent has been widely used in the purification of used cooking oil to improve their quality. This study aimed to determine the quality of cooking oil after adsorbing with tamarindus indica L. seeds. Parameters of the oil quality were color, free fatty acid, peroxide number, and moisture levels. The oil color was determined using UV-Vis spectrophotometer, free fatty acid level using acid-base titration method, peroxide number level using iodometric titration method, and moisture level using gravimetric method. Concentration of adsorbent on the adsorption process varied by 1%, 3% and 5% with two types of cooking oil sample namely traditional cooking oil and brand X cooking oil. The results showed that the oil color became brighter by adding adsorbent. Free fatty acid, peroxide number, and moisture levels decreased by increasing the adsorbent concentration. The best result was obtained at 5% adsorbent concentration. Traditional cooking oil decreased in absorbance from 0.2955 to 0.0610, free fatty acid level decreased from 2.7300% to 0.8300%, peroxide number level decreased from 7 meq/kg to 2.4 meq/kg, and moisture level decreased from 1.5191% to 0.1495%. While for the cooking oil of brand X decreased in absorbance from 0.4355 to 0.1860, free fatty acid level decreased from 1.1900% to 0.6600%, peroxide number level decreased from 4 meq/kg to 1.3 meq/kg, and moisture level decreased from 1.4198% to 0.1197%.